Mast cell concentration and skin wound contraction in rats treated with Brazilian pepper essential oil (Schinus terebinthifolius Raddi) - Estevão,Lígia Reis Moura (2015)
PURPOSE:To evaluate wound contraction and the concentration of mast cells in skin wounds treated with 5% BPT essential oil-based ointment in rats.METHODS:Twenty rats, male, of adult age, were submitted to skin surgery on the right (RA) and left antimeres (LA) of the thoracic region. They were divided into two groups: control (RA - wounds receiving daily topical application of vaseline and lanolin) and treated (LA - wounds treated daily with the topical ointment). The skin region with wounds were collected at days 4, 7, 14 and 21 after surgery. Those were fixed in 10% formaldehyde and later processed for paraffin embedding. Sections were obtained and stained by H.E for histopathology analysis. The degree of epithelial contraction was measured and mast cell concentration were also evaluated.RESULTS:The treated group showed higher mast cell concentrations (p<0.05) associated with increased contraction at day 7 and 14 respectively.CONCLUSION: Ointment containing 5% Brazilian pepper tree oil increases mast cell concentration and promotes skin wound contraction in rats.